Using Eye Tracking and Electroencephalography to assess and evaluate students' cognitive dimensions - Nisiforou, Efi (My University, 2013)
Field dependence-independence (FD/FI) is an important dimension of cognitive styles. The current thesis seeks to identify individuals' level of field independence during visual stimulus tasks processing. It intends to examine brain signals with the use of the EEG neuroimaging method and the eye tracking device. Specifically, it aims to value the relationship between the Hidden Figure Test (HFT) scores, the Eye Tracking metrics and the EEG brain signals device by examine whether and how humans' cognitive behaviour (cognitive abilities) can be identified and clarified through the two cutting edge technologies. Additionally, it seeks to investigate if differences exist among the cognitive groups on a sample of students retrieved from a Public University in Cyprus. The progress achieved so far is outlined and further agenda of the work-in-progress is addressed.
Keywords: Cognitive abilities; Eeg; Eye-tracking; FDI dimension; Hidden figures test; Higher education; Visual stimuli